O eixo movimento da na educação infantil: uma análise do ponto de vista das professoras de uma pré-escola situada em Tocantinópolis(TO) - Marques, Neuzimar Maria Nonato dos Santos (Universidade Federal do Tocantins, 2019)
This research was developed in front of the proposal to elaborate the Course Conclusion Paper entitled "The movement axis in the education of children: an analysis from the point of view of the teachers of a pre-school located in Tocantinópolis - TO. It addresses the importance of the work carried out by teachers of the municipal teaching system of Tocantinópolis in the axis. It is important to note that, for the writing of this, I carried out bibliographic research, observations and field research in the Preschool Mother Eduvirgens, as well as a questionnaire applied to the teachers of the morning shift of said school. In this way, it is important to note how fundamental is the work with the movement axis in Early Childhood Education, since this is important for the development of children from the first month of life and the school is the space where several skills can be contemplated in the process of children.